CHILD ABDUCTION: RECENT JURISPRUDENCE OF THE EUROPEAN COURT OF HUMAN RIGHTS. Issue 1 (29th January 2015) - Unknown
Abstract: This article examines how the European Court of Human Rights has clarified its jurisprudence on how the 1980 Hague Child Abduction Convention Article 13 exceptions are to be applied in a manner that is consistent with Article 8 of the European Convention on Human Rights. It also analyses recent case law of the European Court of Human Rights on how the courts in the EU are to handle child abduction cases where the courts of the habitual residence have made use of their power under Article 11 of Brussels IIa.